The advertisement call of Bokermannohyla flavopicta Leite, Pezzuti & Garcia, 2012 (Anura: Hylidae) from the mountains of Chapada Diamantina, Bahia, Brazil - Rocha, Pedro Carvalho; Thompson, Julia Resende; Leite, Felipe Sá Fortes; Garcia, Paulo Christiano De Anchietta (Zootaxa, 2016)
Bokermannohyla Faivovich, Haddad, Garcia, Frost, Campbell & Wheeler (2005) is a Brazilian treefrog genus currently composed of 32 species (Brandão et al. 2012; Leite et al. 2012; Frost 2015). The genus comprehends four, putatively monophyletic, species groups: B. circumdata, B. claresignata, B. martinsi, and B. pseudopseudis (sensu Faivovich et al. 2005). The B. pseudopseudis group includes nine species: B. alvarengai (Bokermann 1956), B. flavopicta Leite et al. 2012, B. ibitiguara (Cardoso 1983), B. itapoty Lugli & Haddad 2006a, B. oxente Lugli & Haddad 2006b, B. pseudopseudis (Miranda-Ribeiro 1937), B. sagarana Leite et al. 2011, B. sapiranga Brandão et al. 2012, and B. saxicola (Bokermann 1964).